Are Australians ready for warning labels, marketing bans and sugary drink taxes? Two cross-sectional surveys measuring support for policy responses to sugar-sweetened beverages. Issue 6 (27th June 2019) - Miller, Caroline L; Dono, Joanne; Wakefield, Melanie A; Pettigrew, Simone; Coveney, John; Roder, David; Durkin, Sarah J; Wittert, Gary; Martin, Jane; Ettridge, Kerry A
Abstract : Objective: To assess public support for 10 potential policy initiatives to reduce sugar-sweetened beverage (SSB) consumption. Design: A 2014 historical data set, which employed a face-to-face survey in one Australian state (study 1), provided the basis for comparison with our 2017 nationally representative, cross-sectional, computer-assisted telephone interviewing population survey (study 2). Participants: Study 1: South Australians, 15+ years (n=2732); study 2: Australians, 18+ years (n=3430). Primary outcome measures: levels of support for SSB-specific policy initiatives. For the 2017 national study (study 2), demographic characteristics, body mass index, knowledge of potential harms caused by consuming SSBs and SSB consumption were included in multivariable regression analyses. Results: In 2017, all 10 potential policy initiatives received majority support (60%–88% either 'somewhat' or 'strongly' in favour). Initiatives with educative elements or focused on children received high support (>70%), with highest support observed for text warning labels on drink containers (88%) and government campaigns warning of adverse health effects (87%). Higher support was observed for SSB tax paired with using funds for obesity prevention (77%) than a stand-alone tax (60%). Support for policy initiatives was generally greater among those who believed SSB daily consumption could cause health problems in adults (4%–18% absolute difference) and/or in children (8%–26% absolute difference) and lower among SSB high consumers (7+ drinks per week; 9%–29% absolute difference). State-specific data comparison indicated increased support from 2014 to 2017 for taxation (42%vs55%; χ 2 =15.7, p<0.001) and graphic health warnings (52%vs68%; χ 2 =23.4. p<0.001). Conclusions: There is strong public support for government action, particularly regulatory and educational interventions, to reduce SSB consumption, which appears to have increased since 2014. The findings suggest that framing policies as protecting children, presenting taxation of SSBs in conjunction with other obesity prevention initiatives and education focused on the harms associated with SSB consumption will increase support.